2006
DOI: 10.1677/joe.1.06868
|View full text |Cite
|
Sign up to set email alerts
|

Changes in endocrine and neurochemical profiles in neonatal pigs prenatally exposed to increased maternal cortisol

Abstract: Early life environmental factors are able to influence prenatal development and may cause structural and functional effects on hypothalamic-pituitary-adrenal (HPA) axis and neurotransmitter systems in the offspring. These effects seem to be species specific and may depend on the period of gestation when the factors are effective. Elevated maternal cortisol levels are assumed to play a crucial role as a programming factor during prenatal development. Thus, the present study was performed in order to examine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
24
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 74 publications
3
24
0
Order By: Relevance
“…When the data from male and female piglets were combined for analysis, sow treatment had no effect on any litter or piglet characteristic. This is in accordance with previous research results showing that during midgestation neither the authentic stressors of rough handling (Lay et al, 2008) and mixing (Jarvis et al, 2006;Rutherford et al, 2009), nor the artificial stressors ACTH (Haussmann et al, 2000;Schneider et al, 2004;Brussow et al, 2005;Kanitz et al, 2006;Otten et al, 2007) and HCA (Kranendonk et al, 2006) affected gestation length (Haussmann et al, 2000;Jarvis et al, 2006;Kanitz et al, 2006;Kranendonk et al, 2006;Otten et al, 2007;Lay et al, 2008), litter size (Haussmann et al, 2000;Schneider et al, 2004;Brussow et al, 2005;Kanitz et al, 2006;Kranendonk et al, 2006;Otten et al, 2007;Lay et al, 2008;Rutherford et al, 2009), or number of stillborn pigs (Haussmann et al, 2000;Jarvis et al, 2006;Kranendonk et al, 2006;Otten et al, 2007;Lay et al, 2008).…”
supporting
confidence: 93%
“…When the data from male and female piglets were combined for analysis, sow treatment had no effect on any litter or piglet characteristic. This is in accordance with previous research results showing that during midgestation neither the authentic stressors of rough handling (Lay et al, 2008) and mixing (Jarvis et al, 2006;Rutherford et al, 2009), nor the artificial stressors ACTH (Haussmann et al, 2000;Schneider et al, 2004;Brussow et al, 2005;Kanitz et al, 2006;Otten et al, 2007) and HCA (Kranendonk et al, 2006) affected gestation length (Haussmann et al, 2000;Jarvis et al, 2006;Kanitz et al, 2006;Kranendonk et al, 2006;Otten et al, 2007;Lay et al, 2008), litter size (Haussmann et al, 2000;Schneider et al, 2004;Brussow et al, 2005;Kanitz et al, 2006;Kranendonk et al, 2006;Otten et al, 2007;Lay et al, 2008;Rutherford et al, 2009), or number of stillborn pigs (Haussmann et al, 2000;Jarvis et al, 2006;Kranendonk et al, 2006;Otten et al, 2007;Lay et al, 2008).…”
supporting
confidence: 93%
“…Cooper et al, 2009) but their biological mechanisms have not been thoroughly investigated. It is worth noting, however, that several authors have shown that the HPA axis activity was shaped by prenatal influences in a sex-specific manner (Kanitz et al, 2006;Kranendonck et al, 2008;Collier et al, 2011;Óvilo et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The latter is in accordance with findings by Kranendonk et al (2006), who found that piglets born from cortisol-treated sows had a lower peak cortisol response compared with piglets born from noncortisol-treated sows. In addition, piglets born from sows exposed to elevated cortisol concentrations during pregnancy had altered brain neurotransmitter profiles, such as an increased noradrenergic activity in the locus coeruleus region of the hypothalamus, and tended to have reduced glucocorticoid receptor binding (Kanitz et al, 2006).…”
Section: Discussionmentioning
confidence: 99%